Antiinflammatory effect of pterygopalatine blockade for anesthetization in ophthalmic surgery - I. G. Oleshchenko; D. V. Zabolotskiy; T. N. Yureva; N. Y. Senchenko; M. A. Shanturova (Acta Biomedica Scientifica, 2018)
Purpose: to evaluate the effectiveness of analgesic and anti-inflammatory effects of pterygopalatine blockade in the surgical treatment of cataract in children. Materials and methods. A comparative analysis of the efficacy of intraoperative anesthesia and the course of the postoperative period was carried out in 52 patients of two clinical groups that were formed depending on the method of anesthesia. The first clinical group included 26 patients who underwent a pterygopalatine blockade as a regional component of general anesthesia, the second comparison group was formed of 28 patients undergoing retrobulbar blockade. To assess the adequacy of anesthesia, the concentration of plasma cortisol and oxidation-reduction profile was determined before and after the operation, the intensity of the pain syndrome, the extent of the inflammatory reaction of the eye after surgery were assessed. The results showed a decrease in the concentration of cortisol and increased antioxidant capacity of the organism after surgery in patients of the first group. In patients of the 1st clinical group, the Tyndal phenomenon of the 1st degree was revealed in 15.3 % of cases, the remaining patients had no signs of inflammation. Each second patient of 2nd group had a moderate degree of inflammatory reaction, and in 7 % of cases significant exudative phenomena were noted in the form of the Tyndall II degree phenomenon. Conclusion. The use of vesicle blockade in the surgical treatment of cataracts allowed improving the quality of rehabilitation of a patient with congenital cataract, both in the early and late postoperative period.